POST-PANDEMIC GLOBAL LABOUR MIGRATION TRENDS AND ECONOMIC IMPACTS - Zokirov Jamshid Zafar o‘g‘li (Bright Mind Publishing, 2025)
This article presents a systematic analysis of global labour migration processes in the post-pandemic period and their economic impacts. The purpose of the study is to empirically assess changes in migration flows, remittance volumes, and their effects on GDP growth between 2019 and 2024. Using panel data regression models based on data from the International Labour Organization (ILO), the World Bank, and the OECD, the study identifies the role of remittances in economic growth. The results show that a 1% increase in remittances leads to an average increase of 0.18% in GDP. In 2024, the global migrant workforce reached 162 million people, representing 98% of the pre-pandemic level. The Post-Pandemic Recovery Coefficient (PPRC) was estimated at 0.87, indicating a slow but stable economic recovery. The findings demonstrate that labour migration has become a key factor in sustainable development of the international economy in the post-pandemic era.
Keywords: Post-pandemic period, labour migration, remittances, GDP growth, economic recovery, employment, ILO, World Bank, OECD, migrant workers, global economy, economic stability, regional disparities, remittance elasticity, empirical analysis, PPRC, post-COVID, cross-border labour, economic modelling, digital migration.